Efeito mediador da capacidade para inovação na relação entre capacidade de absorção e desempenho organizacional no contexto de franquias - Leal, Bruno Henrique Santana (2020)
This dissertation involves the study of the relationship between absorptive capacity and organizational performance mediated by innovativeness. Based on Cohen and Levinthal's work on absorptive capacity, this dissertation contributes by discussing the relevance and role of knowledge in the context of franchises, aiming to expand knowledge in this area. The focus of this study is justified by the influence of organizational knowledge management on the generation of superior performances compared to other companies in the same industry or sector. For this reason, it was decided to work with the absorptive capacity at the organizational level due to the gap of approaches found in the theoretical bases. To carry out this research, we conducted a quantitative, exploratory-descriptive survey in language franchise networks in the city of São Paulo, which involved 127 respondents. The collected data were processed and validated using the structural equation modeling technique using the SPSS v.15 and PLS-PM 3.0 software. We chose to work with franchise scope because this is a business model where the main strategic asset is knowledge. This, when properly exploited by the franchisor and absorbed by the franchisee, tends to be a source of competitive advantage for the business as a whole. The choice of language school environment was because it was a group with the same end activity. Therefore, with a greater propensity for the homogeneity of respondents, producing more controlled and reliable data for the selected sample. The results obtained suggest that there is partial validity in the central hypothesis of this study, which is the assumption that innovation capacity plays a positive mediator role in the relationship between organizational performance and absorption capacity. The main practical contribution is the finding regarding the role of the exploitation dimension as a relevant factor for superior performance in organizations.